The use of multilevel emotion regulation strategies in the context of critical public events: the more the better? - Zhu, Leling; Yang, Jiemin; Yuan, Jiajin (Frontiers in Psychology, 2024)
Critical public events, like COVID-19, significantly impact individuals' emotional and mental health. People tend to use multi-level emotion regulation strategies (intrapersonal, interpersonal and hyperpersonal) to cope with these events, resulting in various strategy profiles. However, few studies have examined ER strategies from a multilevel perspective. Therefore, this study examines the use of multi-level strategies during COVID-19, and evaluates the effectiveness of these strategies, with a particular interest in identifying strategy profiles promoting mental health.We conducted a two-wave study (an interval of 1 week) using online questionnaires during COVID-19, with an initial sample of 1189 participants and 895 samples completing the surveys across the two waves. Cross-lagged analysis indicated that experiential avoidance was reciprocally positively related to negative emotions while perspective-taking and humorous-meme-saving were reciprocally positively related to life satisfaction or positive emotions over time. Cluster analysis suggested that there were 9 different profiles which scored differently on mental health indicators. Specifically, the use of multi-level strategies tended to be associated with greater positive emotions and life satisfaction while with lower negative emotions and loneliness.This study revealed that the use of multi-level strategies plays a protective role in mental health when facing critical public events. These findings expanded our understanding of how multilevel emotion regulation strategies impact mental health during critical public events and identify protective profiles for mental health.